Research on the Evaluation Index System of the Soil Remediation Effect Based on Blockchain - Menghua Wang; Xuedong Liang; Zhi Li (Land, 2021)
Soil remediation technology has achieved good results at present, but evaluation research on the soil remediation effect is relatively lacking. In the field of soil remediation effect evaluation, there are problems such as unscientific and imperfect indices and the inability to guarantee the authenticity of data. Based on the research results of domestic and foreign scholars and the soil remediation standards of some developed countries, a set of recommended indices for soil remediation evaluation has been formed through the analysis and screening of a large number of documents and the results of expert consultation. However, there are phenomena such as lack of data authenticity, information asymmetry, and low supervision efficiency. Based on the technical characteristics of the blockchain and the current soil remediation effect evaluation requirements, combined with the research results of domestic and foreign scholars and the soil remediation standards of some developed countries, the core technology and corresponding application scenarios were analysed for functional requirements in this paper. The introduction of blockchain technology will improve the authenticity of data and form a decentralized, trustworthy, and traceable supervision model. Finally, an evaluation index system of the soil remediation effect based on blockchain was constructed from the following five aspects: collection of soil remediation indices, the addition of a new blockchain-based soil remediation effect evaluation and supervision model, the determination of index weights, a list of soil remediation effect evaluation indices, and providing feedback and suggestions. Through the application of blockchain technology and the innovative addition of the “regional policy” evaluation index, changes and innovations were made in all aspects of the soil remediation effect evaluation process.